Development of a platform-based approach for the clinical production of HIV gp120 envelope glycoprotein vaccine candidates. Issue 29 (29th June 2021) - Wolfe, Leslie S.; Smedley, James G.; Bubna, Niket; Hussain, Althaf; Harper, Richard; Mostafa, Sigma
Abstract: Preclinical development of vaccine candidates is an important link between the discovery and manufacture of vaccines for use in human clinical trials. Here, an exploratory clinical study utilizing multiple gp120 envelope proteins as vaccine antigens was pursued, which required a harmonized platform development approach for timely and efficient manufacture of the combined HIV vaccine product. Development of cell lines, processes, and analytical methods was initiated with a transmitted founder envelope protein (CH505TF), then applied to produce three subsequent gp120 Env (envelope) variants. Cell lines were developed using the commercially available Freedom CHO DG44 kit (Life Technologies). The fed-batch cell culture production process was based on a commercially-available medium with harmonized process parameters across the variants. A platform purification process was developed utilizing a mixed mode chromatography capture step, with ceramic hydroxyapatite and ion exchange polishing steps. A suite of analytical methods was developed to establish and monitor the Quality Target Profile (QTP), release and long-term stability testing of the vaccine products. The platform development strategy was successfully implemented to produce four gp120 envelope protein variants. In some cases, minor changes to the platform were required to optimize for a particular variant; however, baseline conditions for the processes (cell line type, media & feed system, chromatography resins, and analytical approaches) remained constant, leading to successful transfer and manufacture of all four proteins in a cGMP facility. This body of work demonstrates successful pursuit of a platform development approach to manufacture important vaccine candidates and can be used as a model for other vaccine glycoproteins, such as HIV gp140 trimers or other viral glycoproteins with global health implications. Clinical trial identifier. NCT03220724, NCT03856996.